Mesenchymal stromal cell-derived extracellular vesicle therapy prevents preeclamptic physiology through intrauterine immunomodulation. Issue 2 (28th October 2020) - Taglauer, Elizabeth S; Fernandez-Gonzalez, Angeles; Willis, Gareth R; Reis, Monica; Yeung, Vincent; Liu, Xianlan; Mitsialis, S Alex; Kourembanas, Stella
Abstract: Human umbilical cord-derived mesenchymal stromal cells (MSCs) are a widely recognized treatment modality for a variety of preclinical disease models and have been transitioned to human clinical trials. We have previously shown in neonatal lung disease that the therapeutic capacity of MSCs is conferred by their secreted extracellular vesicles (MEx), which function primarily through immunomodulation. We hypothesize that MEx have significant therapeutic potential pertinent to immune-mediated gestational diseases. Of particular interest is early-onset preeclampsia, which can be caused by alterations of the maternal intrauterine immune environment. Using a heme-oxygenase-1 null mouse model of pregnancy loss with preeclampsia-like features, we examined the preventative effects of maternal MEx treatment early in pregnancy. Heme oxygenase-1 null females (Hmox1 −/− ) or wild-type control females were bred in homozygous matings followed by evaluation of maternal and fetal parameters. A single dose of MEx was administered intravenously on gestational day (GD)1 to Hmox1 −/− females (Hmox1 −/− MEx). Compared with untreated Hmox1 −/− females, Hmox1 −/− MEx-treated pregnancies showed significant improvement in fetal loss, intrauterine growth restriction, placental spiral artery modification, and maternal preeclamptic stigmata. Biodistribution studies demonstrated that MEx localize to a subset of cells in the preimplantation uterus. Further, mass cytometric (CyTOF) evaluation of utero-placental leukocytes in Hmox1 −/− MEx versus untreated pregnancies showed alteration in the abundance, surface marker repertoire, and cytokine profiles of multiple immune populations. Our data demonstrate the therapeutic potential of MEx to optimize the intrauterine immune environment and prevent maternal and fetal sequelae of preeclamptic disease. Abstract : Antenatal administration of human umbilical cord mesenchymal stromal cell-derived extracellular vesicles prevents pregnancy loss, fetal growth restriction, and preeclamptic physiology through multiparameter modulation of intrauterine leukocytes.